A geodatabase of historical landslide events occurring in the highly urbanized volcanic area of Campi Flegrei, Italy - G. Esposito; F. Matano (Earth System Science Data, 2023)
The analysis of geological processes threatening people and properties in a populated region should be based on a comprehensive knowledge of historical events and related characteristics. This type of information is essential for predisposing event scenarios, validating prediction models, and planning risk mitigation measures. Such activities may be more complex in some geological settings, where urban settlements are exposed to multi-hazard conditions. This is the case of the densely populated Campi Flegrei volcanic area located in the Campania region, southern Italy. Here, volcanic and seismic hazards are associated with landslides, floods, and coastal erosion, which are playing a relevant role in the landscape modification. The CAmpi Flegrei LAndslide Geodatabase (CAFLAG), here presented, provides information related to 2302 landslides that occurred in the continental, coastal, and insular sectors of the study area during the 1828–2017 time interval. Data associated with the collected landslide events highlight the characteristics of both landslides and of the affected sites. Most of the cataloged mass movements consist of rock falls affecting rocky slopes formed by lithified volcanic rocks, such as tuff or ignimbrite. In addition, rainfall-induced earth and debris slides translating into debris avalanches or rapid flows are widespread along steep slopes mantled by weakly welded pyroclastic airfall deposits, similarly to other areas of the region. The highest density of landslides is concentrated along the coastline, where mass movements are contributing to the retreat of coastal cliffs, and along inland slopes exposed towards the western directions, where most of the storm systems come from. Temporal information shows peaks of landslides in the years 1986, 1997, and 2005. A total of 127 people lost their lives as a consequence of 53 cataloged landslides, with a frequency of deadly events observed however to have decreased since the early 1980s. This information will be useful to analyze mortality and risk conditions still affecting the population of the Campi Flegrei caldera, which should be fully addressed with advanced knowledge and accurate scenarios. The full database is freely available online at https://doi.org/10.4121/14440757.v2 (Esposito and Matano, 2021).